Pendidikan Islam Masa Rasulullah dan Eksistensi Kuttab serta Masjid dalam Pengembangan Pendidikan Islam - Al Firman Yusra; Zulmuqim Zulmuqim (Jurnal Kawakib, 2022)
Islamic education system refers to the value of Islam. Islamic education foundation located in attitude or outlook on life itself. Which Islam considers life is not an end of all but ground to achieve spiritual goals after life. At the time of the prophet, Islamic education implemented in two periods, Mecca period and Medina period. Mecca period as the initial construction phase of Islamic education and based in Makkah, and Medina period as the center of Islamic learning and activities. The existence of kuttab and mosques aso affected the development of Islamic education. Where Kuttab and Mosque were the start of existing institutions such as madrassa and school and Islamic collages